Glass fiber reinforced plastic cladding method for large-size stern shaft of ship

By using fiberglass putty to fill and mixing resin glue liquid at the copper sleeve joint of the ship's stern shaft, the problem of easy cracking and infiltration of the fiberglass cladding under seawater is solved, and seawater resistance and adhesion strength are improved after the stern shaft cladding.

CN119734434APending Publication Date: 2025-04-01BOHAI SHIPYARD GROUP CORP LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411670852.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the prior art, the fiberglass cladding layer of the stern shaft of the ship is prone to cracking under long-term soaking of seawater, causing seawater to seep and peel off, resulting in problems of poor adhesion and poor sealing.

Method used

By filling with fiberglass putty at the stern copper sleeve joint, the risk of seawater infiltration is reduced, and the solid content and bonding quality of the fiberglass layer are ensured by reasonably modulating the resin glue ratio and improving the winding and covering construction process.

Benefits of technology

It effectively reduces the stern shaft erosion by seawater, improves the seawater resistance and adhesion strength of the fiberglass cladding, and ensures the effect of not corrosion after the stern shaft is coated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119734434A_ABST
    Figure CN119734434A_ABST
Patent Text Reader

Abstract

The present invention proposes a method for coating large-size stern shafts of marine fiberglass. By carrying out the curing and molding process design of the fiberglass coated stern shaft, adjusting a reasonable resin glue ratio, and clarifying the winding and coating construction process, the effect of non-corrosion after the fiberglass coated at the stern shaft copper sleeve joint is achieved; the following steps are included: 1) studying the preparation ratio of the resin glue; 2) improving the coating method of the winding fiber layer during the coating process; 3) using fiberglass putty to fill the parts that are easy to penetrate seawater to reduce the corrosion of the bearing body; 4) controlling the temperature and humidity during the curing process; 5) checking the appearance quality of the coating layer in the coated fiberglass area; 6) making a fiberglass synchronous test plate, the synchronous test plate is naturally cured at room temperature for more than 30 days, or cured at 80°C for more than 5 hours, and after cooling to room temperature, the Barcol hardness of 5 test points on the synchronous test piece is tested, and the average value of the maximum value of a single test is above 20 to be qualified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to composite material molding in the field of ships, and in particular to a fiberglass reinforced plastic coating method for a large-size stern shaft of a ship. Background Art

[0002] At present, the corrosion protection of the stern shaft of ships mainly relies on the coating of non-metallic materials on the surface of the substrate to protect the metal body of the bearing from seawater corrosion. In recent years, many ships have adopted a new process of wrapping the non-working surface of the stern shaft with fiberglass to protect the non-working surface of the stern shaft from seawater corrosion.

[0003] However, the inventors of this application found that the above technology has at least the following technical problems in the process of implementing the technical solution of the invention in the embodiment of this application: After being immersed in seawater for a long time, in a complex environment and under the influence of ship activities, the fiberglass at the edge of the stern shaft cracked. Seawater penetrated into the fabric layer at the edge of the fiberglass, gradually peeling off from the inside to the outside.

[0004] Therefore, when designing the process of the interface at the junction of the FRP paste system, the risk of seawater infiltration should be reduced. Due to the insufficient thickness of the FRP wrapping layer, which is less than 1mm, the unreasonable resin formula, and the unsatisfactory painting process, the FRP wrapping layer and the stern shaft are not firmly bonded, and the overlap between the FRP wrapping layer and the copper sleeve end is not sealed. This embodiment achieves the effect of preventing the stern shaft from corroding after the FRP wrapping is formed by carrying out the stern shaft coating FRP molding process design, adjusting a reasonable resin glue ratio, and clarifying the winding and coating construction process. Summary of the invention

[0005] In order to solve the deficiencies in the prior art, and to address the problems of seawater infiltration and peeling of the fiberglass wrapped on the non-working surface of the stern shaft, the embodiment of the present application provides a method for coating a large-size stern shaft with fiberglass. The method prevents seawater from infiltrating by performing putty anti-corrosion treatment on the gap between the front and rear copper sleeves of the stern shaft, thereby preventing seawater from infiltrating into the fiberglass body, and solving the technical problem of coating the non-working surface of the stern shaft with fiberglass.

[0006] The solution adopted by the embodiment of the present application to solve the technical problem is: The method for coating large-size stern shaft of marine fiberglass is to design the curing and molding process of the stern shaft coated fiberglass, adjust the reasonable resin glue ratio, and clarify the winding and coating construction process, so as to achieve the effect of non-corrosion after the fiberglass coating is formed at the stern shaft copper sleeve joint; the method includes the following steps: 1) Under different temperature and humidity conditions, the formulation ratio of the resin adhesive is studied, and the appropriate gel time is selected according to the different variables to meet the window period requirements of the actual on-board / off-board construction on site; 2) During the coating process, in order to increase the solid content of the winding fiber layer, the coating method of the winding fiber layer is improved to meet the overall appearance quality; 3) Use fiberglass putty to fill the joints of the stern shaft copper sleeve where seawater easily penetrates to reduce the corrosion of the bearing body; 4) After coating, during the curing process, control the temperature and humidity to reduce defects on the FRP surface and meet quality requirements; 5) In the FRP coated area, check the appearance quality of the coating layer. The surface of the FRP layer should be smooth and free of pinholes, glue deficiency, cracks, glue accumulation and damage; 6) Make FRP synchronous test plates, cure them naturally at room temperature for more than 30 days, or cure them at 80℃ for more than 5 hours. After cooling to room temperature, test the Barcol hardness of 5 test points on the synchronous test pieces. The average value of the maximum value of a single test is qualified if it reaches 20.

[0007] Positive effects: The technical solution provided in the embodiments of the present application has at least the following technical effects or advantages: 1. By reasonably controlling the resin ratio, selecting the appropriate gel time, and reducing the bubbles in the glue generated during the construction process, the pinholes and pores of the substrate after molding can be significantly reduced.

[0008] 2. During the winding and covering construction process, by controlling the covering distance between two adjacent layers, it can ensure that each layer of glass fiber cloth is completely infiltrated with the resin, increase the solid content of the glass fiber cloth, and improve the hardness of the FRP after covering molding.

[0009] 3. Use fiberglass putty to fill the joints of the stern shaft copper sleeve to effectively reduce the erosion of the stern shaft by seawater.

[0010] 4. By controlling the construction environment conditions after FRP coating, the occurrence of pinholes and pores can be effectively reduced. The surface of the FRP layer is smooth and bright, which improves the overall quality of FRP coating.

[0011] Through the research on the preparation of resin glue, the research on the construction process of winding and coating, the research on the anti-corrosion filling of the gap of the stern shaft copper sleeve and the research on the control of FRP curing and molding, the appearance of the FRP after the stern shaft coating is effectively improved, and the seawater resistance of the stern shaft is improved to a certain extent. It is suitable for application as a FRP coating method for large-size stern shafts of ships. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0013] Figure 1 This is a schematic diagram of the fiberglass wrapped construction of the stern shaft in this embodiment.

[0014] In the figure, 101. the front end of the rear copper sleeve of the stern shaft; 102. the rear end of the front copper sleeve of the stern shaft; 103. the starting point wrapping the end point; 104. the end point wrapping the end point; 105. the winding starting point; 106. the stern shaft; 107. the winding fiber layer; 108. the core shaft; 109. the machine tool. DETAILED DESCRIPTION

[0015] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Although the embodiments of the present invention have been shown and described, it can be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the attached claims and their equivalents. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention.

[0016] As shown in the figure, the method for coating the large-size stern shaft of a ship with FRP is to design the curing and molding process of the stern shaft coated FRP, adjust the reasonable resin glue ratio, and clarify the winding and coating construction process, so as to achieve the effect of non-corrosion after the stern shaft copper sleeve joint is coated with FRP; the following steps are included: (1) Research on the preparation of resin glue: By properly controlling the resin ratio and selecting an appropriate gel time, the bubbles in the glue generated during the construction process can be reduced, which can significantly reduce the pinholes and pores in the substrate after molding.

[0017] First, calculate the amount of resin, and at the same time, reduce the viscosity of the resin. At room temperature, epoxy resin is a viscous colloid, and it needs to be heated to reduce the viscosity before use. Before construction, the resin needs to be placed in a constant temperature oven at 43±2℃ for more than 4 hours to reach a viscosity range that is convenient for construction. Determine the amount of diluent used according to the workpiece and ambient temperature, and calculate the amount of diluent according to the mass of the epoxy resin. The unit is ml, and the measurement is accurate to 1ml. Use a stirrer to fully stir the resin that has been treated to reduce viscosity, pour the measured diluent into the stirring resin, and stir the stirrer up and down for 5 minutes to avoid a large number of bubbles. Determine the amount of plasticizer used according to the hardness requirements, and calculate the amount of plasticizer according to the mass of the epoxy resin. The unit is ml, and the measurement is accurate to 1ml. Use a stirrer to fully stir the diluted resin, pour the measured plasticizer into the stirring resin, and stir the stirrer up and down for 5 minutes to avoid a large number of bubbles. Formulate the curing agent usage ratio according to the construction area and ambient temperature, and calculate the curing agent dosage according to the mass of epoxy resin. The unit is kg, accurate to 3 decimal places, and accurate to 1g when weighing. Pour the weighed curing agent into the stirring resin system, stir thoroughly for 5 minutes, and move the stirrer up and down to ensure that the curing agent is evenly dispersed; control the resin viscosity at 1000-3000mPa·s to configure the resin glue, and use epoxy resin, diluent, plasticizer and curing agent raw materials in the following proportions in Table 1. The weight ratio is based on 100g of resin. The resin system is configured according to the above ratio to avoid the generation of a large number of bubbles, and the resin glue is made and left to mature for 5 minutes. Before configuration, perform a gel test according to the proportions in the table below, and control the gel time to be 45-60min for the best construction window.

[0018] Table 1

[0019] (2) Research on winding and wrapping construction technology: During the winding and coating construction process, by controlling the coating spacing between two adjacent winding fiber layers 107, it can be ensured that each winding fiber layer 107 is completely infiltrated with the resin, thereby increasing the solid content of the FRP and improving the hardness of the FRP after coating molding.

[0020] 1. Workpiece clamping: Install the stern shaft 106 and the core shaft 108 at both ends of the stern shaft 106 on the chucks at both ends of the machine tool 109. Set up a dial indicator at both ends of the fiberglass-coated shaft diameter, about 200 mm away from the starting point and the end point 103. Start the machine tool 109 to rotate at a constant speed of 1 to 10 rpm. The runout of the stern shaft 106 does not exceed 0.20 mm to ensure good coaxiality and stability.

[0021] 2. Turn on the machine tool 109 and rotate it at a speed of 1 to 10 rpm, and evenly apply a layer of prepared epoxy resin glue on the surface of the stern shaft 106. The winding starting point 105 of the winding fiber layer 107 needs to be about 150 to 200 mm away from both ends of the fiberglass-wrapped area. Wrap the baked winding fiber layer 107 on the stern shaft 106 from the winding starting point 105, and then wrap the end point 103 from the starting point to the end point 104 area and then wrap it in the reverse direction, such as Figure 1 shown.

[0022] 3. During the winding process, the winding pitch of the winding fiber layer 107 is 1 / 4 of the width of the winding fiber layer 107, that is, the workpiece advances 1 / 4 of the width of the cloth tape for one rotation, so as to achieve the effect of wrapping four layers per winding from the beginning to the end. Specifically, in the actual process of cutting the winding fiber layer 107, the width of the cutting winding fiber layer 107 is controlled between 800mm and 1000mm. The width difference between two adjacent layers of glass fiber cloth is controlled between 150 and 200m, and the adjacent two layers are wound with winding fiber layers 107 of different widths to avoid the overlap of the cloth seams of the winding fiber layer 107. Determine the winding starting point of the next layer, start the winding and wrapping of the next layer, and repeat the above wrapping process until the thickness meets the requirements. The winding starting point 105 of the winding fiber layer 107 needs to be about 150 to 200m away from both ends of the wrapped glass fiber reinforced plastic area, and then start to wrap the end point 103 from the starting point to the end point 104 area and then wrap in the opposite direction. The thickness of each wrapped glass fiber reinforced plastic is controlled to be no more than 4mm. During the wrapping process, a scraper is used to remove air bubbles and excess glue, and the scraper glue removal direction is consistent with the workpiece rotation direction to ensure that each layer of the wrapped fiber layer 107 is completely infiltrated with the resin.

[0023] (3) Research on the anti-corrosion filling process of copper sleeve gaps: Using fiberglass putty to fill the joints of the stern shaft copper sleeve can effectively reduce the erosion of the stern shaft by seawater.

[0024] The joints at the rear end 102 of the front copper sleeve of the stern shaft and the front end 101 of the rear copper sleeve of the stern shaft are the two parts of the stern shaft 106 that are most susceptible to corrosion in the seawater environment. Use fiberglass putty for filling here to reduce the erosion of the stern shaft by seawater while ensuring that the same system material as the fiberglass coated stern shaft is used. The putty filling height is flush with the end faces of the front and rear copper sleeves, and the appearance is smooth and smooth. Prepare the fiberglass putty according to the proportion principle in Table 2, based on 100g of resin; adjust the putty viscosity to 15000mPa·s~20000mPa·s, and use an organic solvent to thoroughly clean the surface of the substrate before laying the putty. Control the putty construction window period to 30~45min, the ambient temperature to 10~30℃, and the humidity ≤80%.

[0025] Table 2

[0026] (4) Research on FRP curing and molding control: By controlling the construction environment conditions after FRP coating, the occurrence of pinholes and pores can be effectively reduced, making the surface of the FRP layer smooth and bright, and improving the overall FRP coating quality.

[0027] In order to avoid glue accumulation and sagging quality problems after winding construction, the wound workpiece should be kept rotating at a low speed until the resin undergoes a gel reaction, and then its rotation can be stopped. After the FRP coating construction, the ambient temperature must not be lower than 20℃. When the ambient temperature is lower than 20℃, heating measures should be adopted to avoid quality problems.

[0028] After the coated workpiece is cured for 12 hours, the surface is polished and smoothed with a 60-120 mesh pneumatic sandpaper machine, and then 1-2 coats of resin glue are applied to seal it. At 25°C, after 48 hours of curing, the coated workpiece can be lifted off the machine tool 109 stand.

[0029] In winter, when the ambient temperature is low, the FRP will cure slowly after coating. When using a hot air blower for heating and dehumidification, the air outlet should not be directly facing the coated FRP surface. At this time, because the inner layer resin has not completely reacted, the high temperature promotes the curing reaction of the surface resin, and the solvent in the inner layer resin will evaporate outward, resulting in pinholes and pores on the surface of the FRP. This affects the overall quality of the FRP. At this time, the heating air outlet should be facing away from the shaft surface so that the hot air is evenly dispersed in the construction space, which can effectively reduce the pinholes and pores.

[0030] After the construction is completed, the curing time at 10-30℃ is greater than 30 days, or the curing treatment at 80℃ is more than 5 hours. The Barcol hardness of the FRP surface after coating is greater than 20.

[0031] Stern shaft coated with glass fiber reinforced plastic molding process test verification: (1) First, estimate the amount of resin. Taking the fiberglass coating of the stern shaft 106 as an example, the total mass of the fiberglass coating in the construction area is used as the amount of epoxy resin used in the construction, which can be estimated as: Resin dosage (kg) = nρπDL Where n is the coating thickness, unit: m; D is the diameter of the workpiece in the FRP-coated area, in m; L is the length of the workpiece covered with FRP area, unit: m.

[0032] (2) Prepare the resin glue solution. Use epoxy resin, diluent, plasticizer and curing agent and other raw materials in the proportions shown in Table 1. Based on 100g of resin, prepare the resin system in the above proportions to avoid generating a large number of bubbles and let it stand for 5 minutes. Prepare the fiberglass putty according to the proportions shown in Table 2.

[0033] (3) Use white cotton cloth dipped in xylene, industrial acetone or cleaning gasoline to clean the machined stern shaft and remove the surface oil stains. If there are rust stains on the metal surface, first polish it with 120-360 mesh sandpaper, then remove the oil and clean it until there is no discoloration after wiping with a clean white cotton cloth. Turn on the machine tool 109 and rotate it at a speed of 1-10 rpm, and evenly apply a layer of prepared epoxy resin glue on the surface of the stern shaft 106.

[0034] (4) The winding starting point 105 of the winding fiber layer 107 needs to be about 150 to 200 mm away from both ends of the fiberglass-wrapped area. The baked winding fiber layer 107 is wound around the stern shaft 106 from the winding starting point 105, and then the end point 103 is wrapped from the starting point to the end point 104, and then the area is wound in the reverse direction. When each layer of the winding fiber layer 107 reaches the end point, it must be wrapped in the reverse direction for 150 to 200 mm before finishing, and a layer of epoxy resin glue is applied, and the excess glue is scraped off. Repeat the above steps until the thickness reaches the required thickness.

[0035] The features of this embodiment are as follows: This embodiment conducts process technology research and actual process verification on four aspects of the stern shaft coating glass fiber reinforced plastic process: 1. By reasonably controlling the resin ratio, selecting the appropriate gel time, and reducing the bubbles in the glue generated during the construction process, the pinholes and pores of the substrate after molding can be significantly reduced.

[0036] 2. During the winding and covering construction process, by controlling the covering distance between two adjacent layers, it can ensure that each layer of glass fiber cloth is completely infiltrated with the resin, increase the solid content of the glass fiber cloth, and improve the hardness of the FRP after covering molding.

[0037] 3. Use fiberglass putty to fill the joints of the stern shaft copper sleeve to effectively reduce the erosion of the stern shaft by seawater.

[0038] 4. By controlling the construction environment conditions after FRP coating, the occurrence of pinholes and pores can be effectively reduced. The surface of the FRP layer is smooth and bright, which improves the overall quality of FRP coating.

[0039] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for coating a large-size stern shaft with fiberglass, characterized by: By carrying out the curing and molding process design of the stern shaft coated glass fiber reinforced plastic, adjusting the reasonable resin glue ratio, and clarifying the winding and coating construction process, the effect of non-corrosion of the stern shaft copper sleeve joint after the glass fiber reinforced plastic is coated and formed is achieved; the following steps are included: Step 1: Study the proportion of resin glue under different temperature and humidity conditions, and select the appropriate gel time according to the different variables to meet the window period requirements of actual on-board / off-board construction on site; Step 2: During the coating process, in order to increase the solid content of the wound fiber layer (107), the coating method of the wound fiber layer (107) is improved to meet the overall appearance quality; Step 3: Use fiberglass putty to fill the joints of the stern shaft copper sleeve where seawater easily penetrates to reduce the corrosion of the bearing body; Step 4: After coating, during the curing process, control the temperature and humidity to reduce the defects on the surface of the FRP and meet the quality requirements; Step 5: Inspect the appearance quality of the coating layer in the FRP coated area. The surface of the FRP layer should be smooth and free of pinholes, glue deficiency, cracks, glue accumulation and damage. Step 6: Make a FRP synchronous test plate. The synchronous test plate is naturally cured at room temperature for more than 30 days, or cured at 80°C for more than 5 hours. After cooling to room temperature, test the Barcol hardness of 5 test points on the synchronous test piece. The average value of the maximum value of a single test reaches 20 for passing.

2. The method for coating a large-size stern shaft with fiberglass according to claim 1 is characterized by: In the step 1, the resin glue solution is prepared: By reasonably controlling the resin ratio, the appropriate gel time is selected: before construction, the resin needs to be placed in a constant temperature oven at 43±2℃ for more than 4 hours to reach a viscosity range that is convenient for construction; the resin viscosity is controlled at 1000~3000mPa·s. For the preparation of the resin glue, the raw materials of epoxy resin, diluent, plasticizer and curing agent are used in the following weight proportions: epoxy resin, 100; 662# epoxy resin, 10~20; xylene, 10~20; dibutyl ester, 5~10; anhydrous ethanol, 0~10; coupling agent, 1.2~2.4; defoamer, 1~2; phenolic amine curing agent, 24~30; make the resin glue to avoid the generation of a large number of bubbles, and let it stand for 5 minutes; conduct a gel test before preparation, and control the gel time to be 45~60min as the best construction window.

3. The method for coating a large-size stern shaft with fiberglass according to claim 1 is characterized by: In the step 2, the winding and coating construction process is studied: During the winding and coating construction process, the coating spacing between two adjacent winding fiber layers (107) is controlled to ensure that each winding fiber layer (107) is completely infiltrated with the resin, thereby increasing the solid content of the glass fiber reinforced plastic and improving the hardness of the glass fiber reinforced plastic after coating and molding; include Follow these steps: First, the workpiece is clamped by mounting the stern shaft (106) and the mandrels (108) at both ends of the stern shaft on the chucks at both ends of the machine tool (109), setting up a dial indicator at both ends of the fiberglass-coated shaft diameter, about 200 mm away from the starting point and the end point (103), starting the machine tool (109) to rotate at a constant speed of 1 to 10 revolutions per minute, and the runout of the stern shaft (106) does not exceed 0.20 mm, thereby ensuring good coaxiality and stability; Secondly, the machine tool (109) is turned on and rotated at a speed of 1 to 10 revolutions per minute, and a layer of the prepared epoxy resin glue is evenly applied on the surface of the stern shaft (106); the winding starting point (105) of the winding fiber layer (107) needs to be about 150 to 200 mm away from both ends of the fiberglass coated area, and the baked winding fiber layer (107) is wound on the stern shaft (106) from the winding starting point (105), and then the area is wrapped from the starting point to the end point (103) and then wrapped in the end point (104) and then wound in the reverse direction; Finally, during the winding process, the winding pitch of the winding fiber layer (107) is 1 / 4 of the width of the winding fiber layer (107), that is, the workpiece advances 1 / 4 of the width of the cloth tape after one rotation, so as to achieve the effect of wrapping four layers with each winding from the beginning to the end; two adjacent layers are wound with winding fiber layers (107) of different widths to avoid overlapping of the cloth seams of the winding fiber layers (107); the thickness of each wrapped fiberglass is controlled to be no more than 4 mm; during the winding and wrapping process, a scraper is used to remove bubbles and excess glue, and the scraper glue removal direction is consistent with the workpiece rotation direction to ensure that each layer of the winding fiber layer (107) is completely infiltrated with the resin.

4. The method for coating a large-size stern shaft with fiberglass according to claim 1, characterized in that: In the step 3, the copper sleeve gap anti-corrosion filling process is studied: The joint at the rear end (102) of the front copper sleeve of the stern shaft and the joint at the front end (101) of the rear copper sleeve of the stern shaft are the two parts of the stern shaft (106) that are most susceptible to corrosion in a seawater environment. The joint of the stern shaft copper sleeve is filled with glass fiber reinforced plastic putty to reduce the corrosion of the stern shaft (106) by seawater while ensuring that the same system material as the glass fiber reinforced plastic covering the stern shaft is used. Prepare FRP putty according to the following weight ratio: 6101 epoxy resin, 100; 662# epoxy resin, 10-20; 5034W curing agent, 30-36; talcum powder, 350-465; white carbon black, 115-155; EW210B-100VL alkali-free glass fiber cloth, 5-12; adjust the viscosity of the putty to control at 15000mPa·s~20000mPa·s. Before laying the putty on the substrate, use an organic solvent to thoroughly clean the surface; control the putty construction window period to 30-45min, the ambient temperature to 10-30℃, and the humidity ≤80%.

5. The method for coating a large-size stern shaft with fiberglass according to claim 1 is characterized by: In the step 4, the FRP solidification molding control study: By controlling the construction environment conditions after FRP coating, the occurrence of pinholes and pores can be effectively reduced; the surface of the FRP layer is made smooth and bright, and the overall FRP coating quality is improved; In order to avoid glue accumulation and sagging quality problems after winding construction, the wound workpiece should be kept rotating at a low speed until the resin gels and stops rotating; after the FRP coating construction, the ambient temperature shall not be lower than 20℃; when the ambient temperature is lower than 20℃, heating measures shall be adopted to avoid quality problems; After the coated workpiece is cured for 12 hours, the surface is polished and smoothed with a 60-120 mesh pneumatic sandpaper machine, and then 1-2 coats of resin glue are applied to seal it; after curing for 48 hours at 25°C, the coated workpiece is lifted off the machine tool (109) stand; When the ambient temperature is low in winter, the complete curing of the FRP coating is slow after completion; when using a hot air blower for heating and dehumidification, the air outlet cannot be directly facing the coated FRP surface; at this time, the heating air outlet should be facing away from the shaft surface to allow the hot air to be evenly dispersed in the construction space.

6. The method for coating a large-size stern shaft with fiberglass according to claim 1, characterized in that: In step six, after the construction is completed, the curing time at 10-30°C is greater than 30 days, or the curing treatment at 80°C is more than 5 hours, and the Bacol hardness of the glass fiber reinforced plastic surface after coating is greater than 20.